From ion-hammering to ion-shaping: an historical overview. (June 2015) - Rizza, Giancarlo
Abstract: The objective of this article is to summarize the research activity carried out within the field of amorphous materials submitted to swift heavy-ion irradiation since the opening of the GANIL facilities. In particular, this review focuses on two experimental observations which have created excitement in the swift heavy-ion community for several years: the ion-hammering and the ion-shaping processes. However, this article is neither a comprehensive review nor a tutorial. Indeed, its prime purpose is to give an historical overview of these two phenomena, putting the accent on how a new phenomenon is addressed by the scientific community and how through a difficult trial-and-error approach unsolved problems favor the issue of a coherent description of the phenomenon.